Beliefs in action specification B - Watton, Victor W.; Stone, Robert M. (Dynamic learning, 2016)
Endorsed for Edexcel Trust Victor Watton to maximise every student's potential with his trademark mix of well-paced, focused content coverage and confidence-boosting exam support; tailored to the 2016 Edexcel requirements and brought to you by the market-leading Religious Studies publisher.- Progressively builds students' subject knowledge through accessible explanations of religious and thematic concepts, topics and terms- Helps students learn, retain and revise the key content by following a clear and consistent structure that maps every topic against the specification